Dell Vxrail System Design and Best Practices A Complete Guide to Vxrail Appliance Design and Best Practices - Wu, Victor (Packt Publishing, Limited, 2022)
Design, build, and protect your clusters with ease with VxRail, Dell's hyper-converged infrastructure solution, and this comprehensive in-depth guide Key Features Combine your virtualization systems into one with this comprehensive guide to VxRail Protect against data loss with a variety of backup, replication, and recovery options Take your virtualization skills to the next level thanks to Dell's hyper-converged infrastructure Book Description Virtualized systems are well established now, and their disparate components can be found bundled together in hyper-converged infrastructures, such as VxRail from Dell EMC. Dell VxRail System Design and Best Practices will take you, as a system architect or administrator, through the process of designing and protecting VxRail systems. While this book assumes a certain level of knowledge of VMware, vSphere 7.x, and vCenter Server, you'll get a thorough overview of VxRail's components, features, and architecture, as well as a breakdown of the benefits of this hyper-converged system. This guide will give you an in-depth understanding of VxRail, as well as plenty of practical examples and self-assessment questions along the way to help you plan and design every core component of a VxRail system - from vSAN storage policies to cluster expansion. It's no good having a great system if you lose everything when it breaks, so you'll spend some time examining advanced recovery options, such as VMware Site Recovery Manager and Veeam Backup and Replication. By the end of this book, you will have got to grips with Dell's hyper-converged VxRail offering, taking your virtualization proficiency to the next level. What you will learn Design vSAN storage policies Scale-out and expand clusters Design stretched clusters Protect your system with VMware Site Recovery Manager Discover how to configure EMC RecoverPoint for Virtual Machines Integrate Veeam Backup and Replication with VxRail Set up a vSAN 2-node cluster Who this book is for This book is for system architects, system administrators, or consultants involved in planning and designing VxRail HCI. The reader is expected to have equivalent knowledge and administration experience with VMware vSphere 7. x and vCenter Server 7.x.
Description based upon print version of record. - Designing a VxRail vSAN two-node cluster
Keywords: VMware; Virtual computer systems; Operating systems (Computers); Systèmes virtuels (Informatique); Systèmes d'exploitation (Ordinateurs); operating systems